STUDY OF THERMAL INACTIVATION CLADOSPORIUM CLADOSPORIOIDES α-GALACTOSIDASE - Н. В. Борзова; Л. Д. Варбанець (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2010)
Thermostability of Cladosporium cladosporioides of α-galactosidase was studied in the range of 55 °С and 60 °С. Some of the thermodynamic parameters have been estimated and the mechanism of thermal inactivation has been suggested. Activation energy of transition α-galactosidase subunit from native to denatured state was 165 kJ/M. Stabilization of enzyme molecule in the presence of BSA (19%), glycerol (30–40%), galactose (15%), melibiose, raffinose and stachyose (45%, 21% and 15%) was shown.